Analisis Potensi Sektor Ekonomi di Kabupaten Lamongan Provinsi Jawa Timur - Karima Sharazati (Jurnal Ekonomi Pembangunan, 2021)
The success in the economic development of a region can be evaluated based on its Gross Regional Domestic Product (GRDP). The potential in each area must be maximized effectively to encourage regional economic development. The development of the possibility of a region can contribute significantly to regional progress and become a priority for policies that the government must carry out. The analysis was carried out using the Location Quotient and Shift Shar e methods. There are nine essential sectors or leading sectors from Lamongan Regency in 2015 - 2019. These sectors are the Agriculture, Forestry and Fisheries Sector, Water Supply Sector, Waste Management, Waste and Recycling, Construction Sector, Information and Communication Sector, Sector Real Estate, Government Administration Sector, Land and Compulsory Social Security, Education Services Sector, Health Services, and Social Activities Sector, Other Service Sectors. Optimizing the primary sector will support economic growth in Lamongan Regency. The government of the Lamongan Regency is expected to pay attention to and constantly optimize the facilities and infrastructure or the supporting factors of the non-based sector.